Aspects of reproductive biology of the lesser spiny eel Macrognathus aculeatus (Bloch, 1786) from river Ganga, Uttar Pradesh, India - Faridi, Aysha Aziz; Bano, Farah; Serajuddin, Mohammad (Indian Journal of Fisheries, 2020)
A total of 315 samples of Macrognathus aculeatus (Bloch, 1786) were collected for this study from the river Ganga at Sant Ravidas Nagar, Bhadohi, Uttar Pradesh during June 2016 to May 2017. Chi-square test (χ2) confirmed that the male to female sex ratio was 1:0.93 which was not significantly different from hypothetical ratio of 1:1. The maximum numbers of stage IV gonads were encountered during the month of June indicated its spawning period. Mass and length ratio showed a negative allometric growth (b<3) in males (2.08102), females (2.50212) and for the sexes pooled (2.25371). The maximum and minimum values of condition factor for both the sexes of M. aculeatus were recorded during non-breeding and breeding seasons respectively. The ova diameter of ripe eggs of M. aculeatus ranged between 1.25-1.40 mm during the month of June while the single mean peak value (male =1.40 ± 0.091; female= 4.49 ± 0.059) of the gonado-somatic index of the fish pointed out that the fish has only one breeding season during monsoon. Absolute fecundity varied from 800 to 1510, with an average value of 1247 eggs. Fecundity was found to be highly correlated with the total length (r = 0.9041), body weight (r = 0.8901), ovary length (r = 0.8721) and ovary weight (r 0.9210) which were found to be significant (p<0.001). Keywords: Fecundity, Ganga River, Macrognathus aculeatus, Reproduction